2017
DOI: 10.1371/journal.pone.0182121
|View full text |Cite
|
Sign up to set email alerts
|

Stability of bacteriophages in burn wound care products

Abstract: Bacteriophages could be used along with burn wound care products to enhance antimicrobial pressure during treatment. However, some of the components of the topical antimicrobials that are traditionally used for the prevention and treatment of burn wound infection might affect the activity of phages. Therefore, it is imperative to determine the counteraction of therapeutic phage preparations by burn wound care products before application in patients. Five phages, representatives of two morphological families (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 28 publications
1
43
0
1
Order By: Relevance
“…Over the last years, bacteriophages have been extensively studied as therapeutic agents alone or in conjunction with other therapeutics. In vivo models (Tagliaferri et al, 2019) and a few clinical trials (Merabishvili et al, 2017;Furfaro et al, 2018;Jault et al, 2019) have demonstrated effectiveness of phage treatment against P. aeruginosa and S. aureus infections, without any reported adverse effects. However, little has been published about polymicrobial biofilm infections.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, bacteriophages have been extensively studied as therapeutic agents alone or in conjunction with other therapeutics. In vivo models (Tagliaferri et al, 2019) and a few clinical trials (Merabishvili et al, 2017;Furfaro et al, 2018;Jault et al, 2019) have demonstrated effectiveness of phage treatment against P. aeruginosa and S. aureus infections, without any reported adverse effects. However, little has been published about polymicrobial biofilm infections.…”
Section: Discussionmentioning
confidence: 99%
“…Topical phage and phage-based formulations alone have been useful in the treatment of skin diseases, but some factors can affect their delivery. For instance, the thicker ointment and paste formulations may have added components that can limit phage movement but also the presence of preservative agents in creams and ointments, particularly those with an acidic pH, can negatively impact the effectiveness of phages [159,160].…”
Section: Phage Delivery Systemsmentioning
confidence: 99%
“…These commercial products included creams, gels, suspensions and ointments, and assays involved the dilution of these products 1:1 with phage suspensions. Therefore, the study did not investigate the capacity of intact semi-solid preparations to deliver viable phages, but did demonstrate that some of the active ingredients in the commercial products, such as antibacterial agents, and in particular, acidic compounds, had an adverse effect on phage viability [ 34 ]. While this study provided important insight into possible issues when formulating phages into commercial preparations for bacterial control, it highlighted the potential difficulty in dissociating phage effects from other antibacterial effects when such formulations are used.…”
Section: Stability Of Phages In Semi-solid Preparationsmentioning
confidence: 99%